41CA, 26AL, AND 10BE IN LUNAR BASALT 74275 AND 10BE IN THE DOUBLE DRIVE TUBE 74002/74001 - BULK COMPOSITION, LATE STAGE ACCUMULATION, AND EARLY DIFFERENTIATION OF THE MOON - Fink D.; Klein J.; Middleton R.; Vogt S.; Herzog G.F.; Reedy R.C. (My University, 1998)
We report depth profiles of the cosmogenic radionuclides 10Be, 26Al, and 41Ca in the titanium-rich lunar basalt 74275. The 10Be profile is flat: 10Be activities are confined to a narrow range between 9.6 and 11.2 dpm/kg but are nonetheless consistent with a small contribution of about 1-2 dpm/kg from solar cosmic rays. The 26Al profile shows the steep decrease with increasing depth that is characteristic of nuclides whose production is dominated by solar cosmic rays. 41Ca activities decrease from about 22 dpm/kg at the surface to a minimum of ~9 dpm/kg at a depth of 4.7 g/cm2 and then increase to ~11 dpm/kg at a depth of 15.8 g/cm2. The sharp decrease near the surface identifies for the first time production of 41Ca by solar cosmic rays. We also report 10Be measurements for six samples from lunar core 74002/1. The 10Be activities range from approximately 8 to 14 dpm/kg.We model the production of 10Be, 26Al, and 41Ca in lunar rock 74275 by including published data that indicate a long exposure to galactic cosmic rays at a depth of 140 g/cm2 followed by one at the surface lasting 2.8 Ma. Cosmogenic radionuclide production by galactic cosmic rays, and, in the case of 41Ca, by thermal neutrons is estimated from published measurements and semi-empirical calculations. Our model includes a new calculation of production rates due to solar cosmic rays and incorporates recently published cross section measurements. Although many parameterizations of the flux of solar energetic particles give acceptable fits to the experimental data for 74275, we prefer a best fit obtained for 10Be and 26Al alone, which incorporates an erosion rate of ~2 mm/Ma, a rigidity of 100 MV, and a 4π flux of protons with energies greater than 10 MeV of 89 cm-2 s-1. For 41Ca alone, the corresponding values are 2 mm/Ma, 80 MV, and 198 cm-2 s-1. The differences between the two sets of parameters may reflect uncertainties in the calculations of 41Ca production or a secular change in the solar cosmic ray flux. Calculations for a slab and for a hemispherical knob with a radius of 23 cm yield similar results.